Assessing the potential of community foundation leadership through a new conceptual lens. Issue 2 (14th March 2020) - Lachapelle, Paul
ABSTRACT: Community foundations are emerging as an important and effective method of not only increasing assets and distributing funds in communities but also promoting community dialogue about present needs, future priorities, and the means of collective action. To date, there has been little in the way of synthesizing current scholarship and constructing conceptual models from which to assess community foundation leadership. This research presents a new conceptual lens incorporating themes of leadership, visioning, deliberation, and ownership to design a training program and assess the potential of community foundation leaders and their role in the community. Results show a positive outcome from a 3-year statewide education program focusing on community foundation structure and function and the importance of soft skill development. Implications are discussed focusing on the application and outcomes of similar education programs in other contexts.